Effect of prostacyclin (PGI2) on water and solute transport in the human jejunum. Issue 2 (February 1986) - Moriarty, K J; O'Grady, J; Rolston, D D; Kelly, M J; Clark, M L
Abstract : Prostacyclin is an arachidonic acid metabolite, synthesised throughout the gastrointestinal tract, which has different effects on water and electrolyte transport across a variety of mammalian gastrointestinal epithelia. Using a perfusion technique in the human jejunum of 11 healthy subjects in vivo, the effect of intravenous prostacyclin, 4 ng/kg/min, on jejunal water and solute transport from a glucose electrolyte solution was investigated. In the prostacyclin group (n = 5), prostacyclin was infused intravenously from 70-150 minutes, and buffer administered iv from 0-70 and 150-210 minutes. In the buffer group (n = 6), iv buffer was administered from 0-210 minutes. In the prostacyclin group, net jejunal absorption of water was inhibited from 90-120 min (p less than 0.05), 150-180 min (p less than 0.01) and 180-210 min (p less than 0.01), of sodium was inhibited from 90-120 min (p less than 0.05), 120-150 min (p less than 0.05), 150-180 min (p less than 0.01) and 180-210 min (p less than 0.01), and of chloride was inhibited from 90-120 min (p less than 0.05), 120-150 min (p less than 0.005), 150-180 min (p less than 0.01) and 180-210 min (p less than 0.01). Prostacyclin had no effect on net movement of glucose, potassium or bicarbonate. These results are consistent with a role for prostacyclin in the endogenous humoral regulation of water and electrolyte transport in the human jejunum.